A NUMERICAL AND ANALYTICAL STUDY ON OPTIMIZATION AND EFFICIENCY OF STRUCTURAL FORMS BY TWO-OUTRIGGER IN TALL BUILDINGS (Malaysian Journal of Civil Engineering, 2018)
The selection of a suitable structural system and resist lateral loads in tall buildings plays an important role in structural design. The increase of the heights in the high-rise buildings will be limited because of exceed drift due to lateral loads. The outrigger systems always have been the best choice to limit the lateral deflections in slender buildings. This paper presents analytical and numerical methods to determine optimum location of the outriggers through the height of the building. Optimization and efficiency of the outriggered structural systems were examined in the reduction of the top drift. In the analytical method was used an idealized model as Two- Dimensional (2D) due to horizontal loads. In this regard, Three-Dimensional (3D) building frames were simulated as numerical method by Abaqus/CAE program. Two types conventional forms of the outrigger systems were considered as lateral resisting systems. The numerical models were utilized two outriggers as forms of (a) and (b). Pushover analysis was conducted under uniformly lateral load that was distributed throughout the height. The obtained results by the 2D analytical method shows that the model of the form (a) was optimized when the second outrigger located at 0.58H from the top of the structure while the first outrigger was fixed at the top, in the form (b) was optimized where the outrigger levels were placed at 0.31H and 0.69H, from the top of the building. The results of the 3D modelling by Finite Element Analysis (FEA) indicated that in the form (a) in which the first outrigger is fixed at the top and the second outrigger is optimized at 0.55H from the top of the model. In this way, two outrigger levels of the form (b) were optimized at 0.29H and 0.62H from the top of the structure. The efficiency of the optimized two forms of the outrigger systems in the reduction of the lateral drift at the top of the building by numerical modelling were determined; the efficiency of the outriggers system form (b) is 42% higher than optimized model of the form (a). The 3D Finite Element Analysis (FEA) method for use in the initial design of an outrigger structural system in tall buildings is recommended because of reliable results in compared to the 2D theoretical analysis in order to an optimum design of tall buildings structure.